IT GOVERNANCE AUDIT AT PT PERUSAHAAN GAS NEGARA USING COBIT FRAMEWORK - Servanda, Mahendra Sunt; Mutiara, Achmad Benny (Jurnal Ilmiah Informatika Komputer, 2018)
The use of information and communication technology in a company gives an important contribution for the achievement of business objectives. PT Perusahaan Gas Negara, especially in the Business Solutions and Services Operations (BSSO), plays a significant role in the utilization of information and communication technology assets to PT Perusahaan Gas Negara. It takes a good IT governance for BSSO to improve the efficiency and effectiveness of IT usage. Audit of IT governance maturity using COBIT 4.1. Maturity model level used to determine the maturity level of IT usage in the enterprise with a scale of 0 (non-existent) to 5 (optimized). This study focused on two domains namely Plan and Organise (PO) and Monitor and Evaluate (ME) model to measure the maturity level of IT maturity levels in PT Perusahaan Gas Negara. From this study, the results of the maturity level domain PO is 3.13 and ME is 2.98, it can be given the conclusion that the maturity level of IT governance at PT PGN is in level 3 (defined). At this level means that all the procedures in the company are standardized and documented, but the company is still not able to detect the deviations that have occurred.